2016
DOI: 10.1021/acs.jpcc.6b00136
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Nitrogen-, Boron-Doped Graphene and Co-Doped Graphene as the Potential Catalysts in Nonaqueous Li–O2 Batteries

Abstract: In this work, we perform a first-principles study of graphene, nitrogen-, boron-doped graphene, and codoped graphene as the potential catalysts in nonaqueous lithium− oxygen (Li−O 2 ) batteries. Among the samples studied, borondoped graphene exhibits the lowest discharge and charge overpotentials, suggesting that boron-doped graphene is the best catalyst for both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in nonaqueous Li− O 2 batteries. Another significant finding is that codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(94 citation statements)
references
References 64 publications
5
84
3
Order By: Relevance
“…These results indicate that graphene/ Cu is an excellent catalyst towards both ORR and OER in LiÀO 2 batteries. Then, Tu et al [50] reported that the catalyst of Ndoped graphene shell encapsulating Co is promising for LiÀO 2 batteries and the prediction was confirmed in experiments. Lee et al [51] reported that h-BN/Ni(111) can be a good cathode catalyst for LiÀO 2 batteries.…”
Section: Orr and Oer On Cathode Catalystsmentioning
confidence: 90%
See 1 more Smart Citation
“…These results indicate that graphene/ Cu is an excellent catalyst towards both ORR and OER in LiÀO 2 batteries. Then, Tu et al [50] reported that the catalyst of Ndoped graphene shell encapsulating Co is promising for LiÀO 2 batteries and the prediction was confirmed in experiments. Lee et al [51] reported that h-BN/Ni(111) can be a good cathode catalyst for LiÀO 2 batteries.…”
Section: Orr and Oer On Cathode Catalystsmentioning
confidence: 90%
“…Jing and Zhou [45] systematically investigated the initial ORR processes on the surface of various kinds of N-doped (graphitic N, pyridinic N, and pyrrolic-like N) graphene ( Figure 5) in comparison with those on the pristine graphene based on DFT computations. Jiang et al [48] also reported that B-doped graphene is a good catalyst for LiÀO 2 batteries. The in-plane pyridinic N could reduce the overpotential more effectively than the graphitic N, facilitating the nucleation of Li 2 O 2 , which can be attributed to the electron-withdrawing configurations.…”
Section: Orr and Oer On Cathode Catalystsmentioning
confidence: 99%
“…The first pioneering computational studies on chemically modified graphene as an electrocatalyst focus on the nitrogen‐doped graphene, but suggests that chemical doping, in general, could be one of the key factors to build an excellent carbon‐based electrocatalyst. Indeed, further computational studies on O 2 adsorption, which is the first step of ORR, or on the full electrochemical process, have followed dealing with both metal and non‐metal impurities, edges as well as carbon vacancies . For example, bulk‐substituted N‐doped graphene was found to require an overpotential for ORR of 0.72 V, while edge‐substituted N‐doped nanoribbons are characterized by lower overpotentials both for ORR and OER .…”
Section: Computational Electrochemistrymentioning
confidence: 99%
“…[9][10][11][12] However,t he discharge products,s uch as Li 2 O 2 and LiO 2 ,c ould react with carbon to form an insulating lithium carbonate layer,r esulting in cathode passivation and capacity fading in Li-O 2 batteries. [9][10][11][12] However,t he discharge products,s uch as Li 2 O 2 and LiO 2 ,c ould react with carbon to form an insulating lithium carbonate layer,r esulting in cathode passivation and capacity fading in Li-O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-basedm aterials, ap romising candidate for the air electrode, have been extensivelys tudied. [9][10][11][12] However,t he discharge products,s uch as Li 2 O 2 and LiO 2 ,c ould react with carbon to form an insulating lithium carbonate layer,r esulting in cathode passivation and capacity fading in Li-O 2 batteries. [13,14] This problem can be circumvented by replacing carbon with other noncarbonm aterials.…”
Section: Introductionmentioning
confidence: 99%